Perlindungan Hukum Terhadap Pekerja Disabilitas: Tinjauan Undang – Undang Cipta Kerja - Halim, Bobby Christian (Bacarita Law Journal, 2025)
Legal protection for workers with disabilities in Indonesia is a crucial issue in achieving equality and inclusion in the workplace. Law Number 8 of 2016 on Persons with Disabilities and Law Number 11 of 2020 on Job Creation mandate companies to employ persons with disabilities. Private companies are required to employ at least 1% of workers with disabilities, while government institutions must employ a minimum of 2%. This obligation is not merely about fulfilling quotas but must also be accompanied by the provision of an accessible work environment, such as disability-friendly infrastructure, assistive work tools, and policies that support their career development. This study aims to analyze the legal protection for workers with disabilities based on the Job Creation Law. The research method used is normative legal research with a statute approach. This study examines how regulations guarantee the rights of workers with disabilities, including equal wages, protection from discrimination, and reasonable workplace accommodations. The findings indicate that the Job Creation Law strengthens the rights of workers with disabilities by ensuring equal pay with other workers who have similar responsibilities. Furthermore, regulatory oversight and law enforcement mechanisms are established, including administrative sanctions for companies that fail to comply. As an incentive, the government provides tax relief and facility assistance for companies that actively employ persons with disabilities. This study concludes that although regulations are in place, their effectiveness still needs to be improved through strict supervision and broader education for the business sector.